Anatomical study of the branching pattern of the right coronary artery - Riya Abraham,; Deepthi B,; Neenu A George, (Asian Journal of Medical Sciences, 2024)
Background: The frequency of coronary artery disease is increasing nowadays. A detailed idea about the normal and variant anatomy of coronary arteries is essential in the management of various heart diseases, especially coronary bypass surgeries. Aims and Objectives: The aims and objectives of the study are to study the branching pattern of the right coronary artery (RCA). Materials and Methods: One hundred adult heart specimens were collected from the Department of Anatomy, Government Medical College, Kottayam. The specimens were fixed in formalin and the RCA was traced from origin to termination. Emphasis was given to the variations in branching patterns. Results: The incidence of a third coronary artery was 20%. The origin of the sinoatrial (SA) nodal artery from both the RCA and the left circumflex artery was 7%. The incidence of the double posterior descending artery was 9%. Short RCA terminating near the right margin was 4%. Long RCA reaching up to left margin was 4%. Conclusion: The SA nodal artery arose from RCA in the majority of cases. The posterior descending artery was single in most of the cases and its most common site of termination was up to three-quarters of the way down the posterior interventricular sulcus. In about half of the cases, the Atrioventricular nodal artery took origin from RCA. There was no statistically significant association between origin of the conus artery and gender. A statistically significant association was not observed between the origin of SA Nodal artery and gender.